Preparation method of humic acid

Through electrochemical reaction methods, the electrolytic system of nickel sheets and platinum sheets is used to convert lignite into humic acid, which solves the low yield problem caused by long-term reactions in the prior art, and achieves the effect of high yield and mild operation.

CN119684629APending Publication Date: 2025-03-25INNER MONGOLIA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411989176.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing humic acid preparation methods require higher temperatures and long-term reactions, resulting in a lower yield of humic acid.

Method used

The electrochemical reaction system of the electrolytic reaction system is used to filter and adjust the pH to obtain humic acid.

Benefits of technology

It improves the yield of humic acid, has mild operating conditions, saves energy, and is simple to operate, clean and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223256790000061
    Figure BDA0005223256790000061
Patent Text Reader

Abstract

The invention discloses a preparation method of humic acid. The preparation method comprises the following steps: (1) carrying out an electrolytic reaction on an electrochemical reaction system which takes a nickel sheet as an anode, a platinum sheet as a cathode and a dispersion liquid containing lignite particles, alkali metal hydroxide and water as an electrolyte to obtain an electrolytic product; wherein the electrolysis voltage ranges from 1.3 V to 2.5 V, the electrolysis time ranges from 3.5 h to 15 h, and the particle size of lignite particles ranges from 200 meshes to 400 meshes; (2) filtering the electrolysis product to obtain a liquid product; after the pH of the liquid product is adjusted to be smaller than or equal to 4, solid-liquid separation is conducted, and humic acid is obtained. The preparation method provided by the invention can improve the yield of humic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing humic acid. Background Art

[0002] Humic acid is a kind of irregular polyphenol polymer with widespread existence and multiple functional groups. The main oxygen-containing functional groups are carboxyl, hydroxyl, methoxy, keto, enol, etc. The various functional groups contained in humic acid give it a variety of properties, such as adsorption, redox, cation exchange capacity, physiological activity and good carbon fixation function, etc. It is widely used in industry, environmental protection, materials, biomedicine, agricultural production, cosmetics, daily necessities and other fields. Lignite is a low-rank coal with abundant reserves. However, due to its rich oxygen-containing functional groups and pore structure, it has a high water content, which affects its combustion efficiency.

[0003] CN101544675A discloses a dry method for producing sodium (potassium) humate, which comprises the following steps: sampling weathered coal and / or lignite for analysis and testing, and calculating the humic acid content; taking weathered coal or lignite and putting them into a semi-closed reaction tower, and at the same time, adding 5-20% of the weight of weathered coal and / or lignite according to the humic acid content in the weathered coal or lignite, stirring evenly, heating with steam, and controlling the temperature at 85-120°C for 12-36 hours, and then aging at 60-120°C for 5-10 hours. The method needs to be carried out at a relatively high temperature, and the reaction time is relatively long, the reaction conditions are relatively harsh, and the yield of sodium (potassium) humate is relatively low.

[0004] CN102747381A discloses a method for preparing humic acid by electrochemical oxidation of lignite, wherein lignite is ball-milled, mixed, and sieved to obtain a coal sample with a particle size of 80 to 200 mesh; the coal sample is weighed and added to an alkaline solution to prepare a coal slurry suspension, and ultrasonic treatment is performed to disperse the coal particles evenly to obtain a coal slurry; an electrochemical reactor is used for the experiment, the prepared coal slurry is added to the anode area, and the alkaline solution of the same concentration is added to the cathode area; a three-electrode system is used, the anode is the working electrode, the cathode is the counter electrode, and a saturated calomel electrode is used as a reference electrode; after the electrolysis reaction is completed, the anode slurry is centrifuged, and the obtained upper layer solution is acidified to pH=3 with concentrated sulfuric acid, filtered, and humic acid is obtained. The method uses a three-electrode system to prepare humic acid, and the yield of humic acid is low. Summary of the invention

[0005] In view of this, an object of the present invention is to provide a method for preparing humic acid, which can improve the yield of humic acid.

[0006] The present invention achieves the above-mentioned purpose through the following technical solutions.

[0007] The present invention provides a method for preparing humic acid, comprising the following steps:

[0008] (1) performing an electrolytic reaction in an electrochemical reaction system using a nickel sheet as an anode, a platinum sheet as a cathode, and a dispersion containing lignite particles, an alkali metal hydroxide, and water as an electrolyte to obtain an electrolytic product; wherein the electrolysis voltage is 1.3 to 2.5 V, the electrolysis time is 3.5 to 15 hours, and the particle size of the lignite particles is 200 to 400 meshes;

[0009] (2) filtering the electrolysis product to obtain a liquid product; adjusting the pH of the liquid product to be less than or equal to 4, and performing solid-liquid separation to obtain humic acid.

[0010] According to the preparation method of the present invention, preferably, in the dispersion, the mass molar ratio of the lignite particles to the alkali metal hydroxide is 3-9 g / mol, and the molar volume ratio of the alkali metal hydroxide to water is 0.5-3 mol / L.

[0011] According to the preparation method of the present invention, preferably, the alkali metal hydroxide is selected from one or more of sodium hydroxide and potassium hydroxide.

[0012] According to the preparation method of the present invention, preferably, the electrolysis reaction temperature is 15-38°C.

[0013] According to the preparation method of the present invention, preferably, the electrolyte is kept in a stirring state during the electrolysis process, and the rotation speed of the device for stirring the electrolyte is 100 to 400 r / min.

[0014] The preparation method according to the present invention preferably further comprises the following steps:

[0015] The lignite is dried at 90-150° C. and then crushed to obtain crushed lignite; the crushed lignite is screened to obtain lignite particles.

[0016] According to the preparation method of the present invention, preferably, in step (2), concentrated sulfuric acid is used to adjust the pH of the liquid product; and solid-liquid separation is performed by centrifugation, with a centrifugal speed of 7000 to 11000 r / min.

[0017] According to the preparation method of the present invention, preferably, in step (2), the liquid product after pH adjustment is allowed to stand for more than 5 hours, and then the solid-liquid separation is performed to obtain a solid product; and the solid product is dried at 70-100° C. to obtain humic acid.

[0018] According to the preparation method of the present invention, preferably, no partition is provided in the electrolytic cell used, and the electrolyte used by the cathode and the anode is the same.

[0019] According to the preparation method of the present invention, preferably, the humic acid yield is ≥ 80 wt %.

[0020] The preparation method of the present invention can convert the abundant lignite into humic acid with high added value and has a high yield. Furthermore, the preparation method of the present invention is simple to operate, has mild conditions, and is clean and pollution-free. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0022] The method for preparing humic acid of the present invention comprises the following steps: (1) an electrolysis step; and (2) a post-treatment step. In certain embodiments, the method further comprises a step of preparing lignite particles. Each step is described in detail below.

[0023] <Electrolysis Procedure>

[0024] The present invention uses a nickel sheet as an anode, a platinum sheet as a cathode, and a dispersion containing lignite particles, alkali metal hydroxide and water as an electrolyte to perform an electrolytic reaction in an electrochemical reaction system to obtain an electrolytic product.

[0025] The anode of the present invention is a nickel sheet, and the cathode is a platinum sheet. The present invention finds that such a cathode and anode arrangement is helpful to improve the yield of humic acid.

[0026] The present invention uses a dispersion containing lignite particles, alkali metal hydroxide and water as the electrolyte. Preferably, the dispersion consists of lignite particles, alkali metal hydroxide and water.

[0027] The particle size of the lignite particles is 200 to 400 meshes. Specifically, the above range includes the lower limit value, but does not include the upper limit value, i.e., 200 (inclusive) to 400 (exclusive) meshes. The present invention finds that the particle size of the lignite particles has an important influence on the yield of humic acid, which may be because the appropriate particle size helps to control the degree of oxidation, prevent the occurrence of incomplete oxidation or over-oxidation, and improve the yield of humic acid.

[0028] The moisture content in the lignite may be 1 to 10 wt %, preferably 2 to 8 wt %, and more preferably 3 to 5 wt %. The moisture content may be calculated on an air-dried basis.

[0029] The ash content in the lignite may be 10 to 25 wt %, preferably 12 to 20 wt %, and more preferably 14 to 16 wt %. The ash content may be calculated on a dry basis.

[0030] The volatile matter content in the lignite may be 35 to 55 wt %, preferably 40 to 50 wt %, and more preferably 45 to 48 wt %. The volatile matter content may be calculated on a dry ash-free basis.

[0031] The H / C ratio in lignite may be 0.03 to 0.12; preferably 0.05 to 0.1; more preferably 0.07 to 0.08.

[0032] The carbon content in lignite may be 55 to 75 wt %; preferably 60 to 70 wt %; more preferably 65 to 68 wt %.

[0033] The hydrogen content in lignite may be 1 to 9 wt %; preferably 2 to 7 wt %; more preferably 3 to 5 wt %.

[0034] The nitrogen content in lignite may be 1 to 8 wt %; preferably 2 to 6 wt %; more preferably 3 to 4 wt %.

[0035] The sulfur content in lignite may be 0.8 to 5 wt %; preferably 1 to 4 wt %; more preferably 2 to 3 wt %.

[0036] The oxygen content in lignite may be 15 to 35 wt %; preferably 17 to 30 wt %; more preferably 20 to 25 wt %.

[0037] The content of each element in lignite can be calculated on a dry basis.

[0038] The alkali metal hydroxide can be selected from one or more of sodium hydroxide and potassium hydroxide. According to one embodiment of the present invention, the alkali metal hydroxide is sodium hydroxide.

[0039] In the dispersion, the mass molar ratio of lignite particles to alkali metal hydroxide can be 3-9 g / mol, preferably 5-8 g / mol, and more preferably 6-7 g / mol, which helps to increase the yield of humic acid.

[0040] In the dispersion, the molar volume ratio of the alkali metal hydroxide to water is 0.5 to 3 mol / L, preferably 0.8 to 2 mol / L, and more preferably 1 to 1.5 mol / L, which helps to increase the yield of humic acid.

[0041] The cathode and anode of the electrolytic cell used in the present invention are interconnected. No partition (such as a diaphragm, etc.) is provided between the cathode and the anode. The electrolyte used by the cathode and the anode is the same.

[0042] The electrolysis voltage is 1.3 to 2.5 V, preferably 1.5 to 2.2 V, and more preferably 1.8 to 2 V. This helps to increase the yield of humic acid.

[0043] The electrolysis temperature can be 15 to 38° C., preferably 20 to 35° C., and more preferably 25 to 30° C. The present invention performs electrolysis at room temperature, with mild reaction conditions and energy saving.

[0044] The electrolysis time is 3.5 to 15 hours, preferably 4 to 10 hours. In some embodiments, the electrolysis time is 4 to 6 hours. In other embodiments, the electrolysis time is 8 to 10 hours. This can not only increase the yield of humic acid, but also save energy.

[0045] The electrolyte is kept in a stirring state during the electrolysis process. The rotation speed of the device for stirring the electrolyte can be 100 to 400 r / min, preferably 200 to 300 r / min.

[0046] <Post-processing steps>

[0047] The present invention filters the electrolysis product to obtain a liquid product; after adjusting the pH of the liquid product to be less than or equal to 4, the solid and liquid are separated to obtain humic acid. Preferably, the liquid product is adjusted to a pH of ≤3.

[0048] The pH of the liquid product can be adjusted by using concentrated sulfuric acid, which refers to a sulfuric acid aqueous solution with a mass fraction greater than or equal to 70%.

[0049] The liquid product after pH adjustment can be left to stand for more than 5 hours, preferably for more than 8 hours, and more preferably for more than 12 hours. In some embodiments, the liquid product is left to stand for 10 to 15 hours.

[0050] The liquid product after pH adjustment can be separated into solid and liquid by centrifugation. The centrifugal speed can be 7000-11000 r / min, preferably 9000-10000 r / min.

[0051] The solid product obtained by solid-liquid separation is dried to obtain humic acid. The drying temperature may be 70 to 100° C., preferably 80 to 90° C. The drying may be carried out in a drying oven.

[0052] <Step of Preparing Lignite Particles>

[0053] The lignite is dried and then crushed to obtain crushed lignite; the crushed lignite is screened to obtain lignite particles.

[0054] The drying temperature may be 90 to 150°C, preferably 100 to 120°C, and more preferably 100 to 110°C.

[0055] The crushed lignite can be screened using a standard sieve. Specifically, the crushed lignite is passed through a first standard sieve to collect the undersize. The undersize is passed through a second standard sieve to collect the oversize. The mesh number of the first standard sieve is smaller than the mesh number of the second standard sieve.

[0056] Here are the raw materials:

[0057] The composition of lignite is as follows:

[0058]

[0059] Note: ad: air-dried basis; d: dry basis; daf: dry ash-free basis; *: calculated by subtraction method; M: moisture; A: ash; V: volatile matter

[0060] Here is the test method:

[0061] The humic acid yield (I) was calculated using the following formula:

[0062] I=m1 / m2×100%

[0063] Here, I represents the humic acid yield (wt%), m1 represents the mass of the obtained humic acid (g), and m2 represents the mass of the lignite (g).

[0064] Examples 1 to 4 and Comparative Examples 1 to 6

[0065] The lignite was dried at 100° C. for 12 hours and then crushed by a crusher to obtain crushed lignite. The crushed lignite was sieved by a standard sieve to obtain lignite particles.

[0066] An electrochemical reaction system with a nickel sheet as an anode, a platinum sheet as a cathode, and a dispersion liquid composed of lignite particles, sodium hydroxide and water as an electrolyte is subjected to an electrolytic reaction to obtain an electrolytic product. In the electrolyte, the mass molar ratio of lignite particles to sodium hydroxide is 6g / mol, and the molar volume ratio of sodium hydroxide to water is 1mol / L. The electrolysis temperature is 25°C, and the electrolysis voltage is 1.93V. During the electrolysis process, the electrolyte is kept in a stirring state, and the speed of the device for stirring the electrolyte is 200r / min.

[0067] The electrolysis product is filtered to obtain a liquid product. Concentrated sulfuric acid is added to the liquid product to adjust the pH to less than 3 to obtain a pH-adjusted liquid product. The pH-adjusted liquid product is allowed to stand overnight and then centrifuged at a speed of 9600 r / min to obtain a solid product. The solid product is dried in a drying oven at a temperature of 80° C. to obtain humic acid.

[0068] The particle size, electrolysis time and humic acid yield of lignite particles are shown in Table 1.

[0069] Table 1

[0070] Serial number Particle size of lignite particles (mesh) Electrolysis time (h) Humic acid yield (wt%) Example 1 200~400 4 82.15 Example 2 200~400 6 83.12 Example 3 200~400 8 83.33 Example 4 200~400 10 85.67 Comparative Example 1 80~100 4 58.33 Comparative Example 2 100~200 4 52.25 Comparative Example 3 More than 400 mesh 4 63.67 Comparative Example 4 200~400 1 44.33 Comparative Example 5 200~400 2 60.52 Comparative Example 6 200~400 3 72.21

[0071] Comparative Example 7

[0072] Except that no electricity was supplied, the rest was the same as in Example 1. The yield of humic acid was 20.37 wt%.

[0073] Comparative Example 8

[0074] Except that the platinum sheet was used as the anode, the rest was the same as in Example 1. The yield of humic acid was 49.82 wt%.

[0075] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A method for preparing humic acid, characterized in that: The steps include: (1) performing an electrolytic reaction in an electrochemical reaction system using a nickel sheet as an anode, a platinum sheet as a cathode, and a dispersion containing lignite particles, an alkali metal hydroxide, and water as an electrolyte to obtain an electrolytic product; wherein the electrolysis voltage is 1.3 to 2.5 V, the electrolysis time is 3.5 to 15 hours, and the particle size of the lignite particles is 200 to 400 meshes; (2) filtering the electrolysis product to obtain a liquid product; adjusting the pH of the liquid product to be less than or equal to 4, and then separating the solid and the liquid to obtain humic acid.

2. The preparation method according to claim 1, characterized in that: In the dispersion, the mass molar ratio of lignite particles to alkali metal hydroxide is 3-9 g / mol, and the molar volume ratio of alkali metal hydroxide to water is 0.5-3 mol / L.

3. The preparation method according to claim 1, characterized in that: The alkali metal hydroxide is selected from one or more of sodium hydroxide and potassium hydroxide.

4. The preparation method according to claim 1, characterized in that: The electrolysis reaction temperature is 15-38°C.

5. The preparation method according to claim 1, characterized in that: During the electrolysis process, the electrolyte is kept in a stirring state, and the rotation speed of the device for stirring the electrolyte is 100 to 400 r / min.

6. The preparation method according to claim 1, characterized in that: The following steps are also included: The lignite is dried at 90-150° C. and then crushed to obtain crushed lignite; the crushed lignite is screened to obtain lignite particles.

7. The preparation method according to claim 1, characterized in that: In step (2), concentrated sulfuric acid is used to adjust the pH of the liquid product; solid-liquid separation is performed by centrifugation, and the centrifugal speed is 7000-11000 r / min.

8. The preparation method according to claim 1, characterized in that: In step (2), the liquid product after pH adjustment is allowed to stand for more than 5 hours, and then the solid-liquid separation is carried out to obtain a solid product; the solid product is dried at 70-100° C. to obtain humic acid.

9. The preparation method according to claim 1, characterized in that: The electrolytic cell used is not provided with a partition, and the electrolyte used by the cathode and the anode is the same.

10. The preparation method according to any one of claims 1 to 9, characterized in that: The humic acid yield is ≥80wt%.

Citation Information

Patent Citations

  • Method for producing sodium humate (potassium humate) with drying method

    CN101544675A

  • Method for preparing humic acid through lignite electrochemical oxidation

    CN102747381A